Fracture resistance of prefabricated versus custom-made zirconia crowns after thermo-mechanical aging: an in-vitro study - Osama Ibrahim El Shahawy; Maha Moussa Azab (BMC, 2022)
Abstract Background Prefabricated zirconia crowns for a young permanent molar is a child-friendly solution for restoring a permanent molar at a young age. This in-vitro study aimed to compare the fracture resistance of prefabricated versus custom-made permanent molar crowns. Methods 16 identical resin dies were fabricated to receive permanent molar zirconia crowns, dies were divided into 2 groups, 1) received perfricated crowns, 2) custom-made crowns. Thermo-dynamic cycling was performed to simulate 6 months in the oral cavity, Fracture resistance of each group was assessed by applying increasing load till fracture. Data were tested for normality using Shapiro-Wilk and Levene's tests. Data were analyzed using independent t test. Results No statistically significant difference was found between fracture resistance of prefabricated and custom-made crowns (1793.54 ± 423.82) and (1987.38 ± 414.88) respectively. 3 crowns of the custom-made group fractured with the underlying die, versus zero dies fractured in the prefabricated group. Conclusions Prefabricated permanent molars zirconia crowns can perform as well as custom-made crowns for an adult in terms of fracture resistance, it is suitable for children and can withstand the occlusal forces of an adult.